Clinicopathologic characteristics and survival outcomes in neuroendocrine carcinoma of the ovary. Issue 2 (2nd December 2019) - Zhu, Ying; Meng, Fanlong; Fang, Huibin; Zhang, Zhigang; Wang, Liang; Zheng, Wei
Abstract : Objective: Neuroendocrine tumors are rare in the ovary. Definitive epidemiologic and prognostic information for neuroendocrine carcinoma of the ovary is lacking. This retrospective population-based study aimed to elucidate the demographic and clinicopathologic characteristics of neuroendocrine carcinoma of the ovary. Methods: Patients with neuroendocrine carcinoma of the ovary diagnosed between January 1994 and December 2014were identified from the Surveillance, Epidemiology, and End Results (SEER) database of the National Cancer Institute. Cancer-specific survival was calculated by Kaplan-Meier plots and comparisons were performed using the log-rank test. A Cox hazard regression analysis was performed to identify independent predictors of cancer-specific survival in patients with neuroendocrine carcinoma of the ovary. Results: A total of 166 patients were included, and 21.1% were younger than 50 years old. The majority of patients (59.6%) presented with unilateral tumors. Patients with neuroendocrine carcinoma of the ovary had significantly worse survival compared with most subtypes of epithelial ovarian cancer (including serous, endometrioid, mucinous, and clear cell), and similar to ovarian carcinosarcoma. The rate of cancer-specific survival was significantly different under the SEER histologic stages. Patients with low-grade neuroendocrine carcinoma of the ovary had longer average survival times than those with high-grade neuroendocrine carcinoma of the ovary (HR 3.43, 95% CI 1.56 to 7.54, p=0.002). Patients with neuroendocrine carcinoma of the ovary who underwent surgery had significantly better survival than those who did not undergo surgery (HR 2.23; 95% CI 1.45 to 3.43, p=<0.05). Conclusions: Early clinical stage and low tumor grade independently predict better survival in patients with neuroendocrine carcinoma of the ovary. Surgery may be a useful therapy for neuroendocrine carcinoma of the ovary.